A Design of isolated amplifier using feedback signal for solving non- linear of opto coupler device - Choeisai, Krit; Prasertcharoensuk, Vichai; Budboonchu, Jirawat (Engineering and Applied Science Research, 2015)
This paper presents a design of isolated amplifier using feedback signal for solving non-linear of optocoupler device. Optocoupler device is usually used in isolated amplifier. It is used to isolate electricity in order to protect high voltage and ground loop. Since optocoupler are non-linear device, feedback signal is used to solve the problem of non-linear.The result showed that feedback signal could compensate the non-linear of optocoupler device by using a simple circuit and the bandwidth of frequency was 12 kHz.